The Impact of Human Development Index on Poverty Rates in Indonesia: Panel Data Analysis of 34 Provinces, 2015-2023 - Dede Arseyani pratamasyari; Irham pakawaru; Nuriatullah; Noor Riefma Hidayah; Rizki Amalia (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Poverty remains a critical development challenge in Indonesia despite significant economic growth over the past decades. This study examines the impact of Human Development Index (HDI) on poverty rates across 34 Indonesian provinces during 2015-2023. Using balanced panel data regression with fixed effects model (selected through Chow, Hausman, and Lagrange Multiplier tests), we analyze how HDI, GDP per capita, and open unemployment rate affect poverty levels. The sample comprises 306 observations (34 provinces × 9 years) sourced from Statistics Indonesia (BPS). Results indicate that HDI has a significant negative effect on poverty (coefficient: -0.0487, p<0.01), suggesting that a 10-point increase in HDI reduces poverty by approximately 0.49 percentage points. GDP per capita shows a stronger elasticity (coefficient: -0.5623, p<0.01), with 1% increase in GDP per capita reducing poverty by 0.562 percentage points. The open unemployment rate exhibits a positive but marginally significant relationship with poverty (coefficient: 0.0876, p<0.10). The fixed effects model explains 74.2% of poverty variation (R² = 0.742), indicating that human capital development through HDI improvements is crucial for sustainable poverty reduction. Policy recommendations include enhancing education quality, expanding health services coverage, promoting inclusive economic growth, and creating productive employment opportunities. This study contributes to the literature by providing comprehensive evidence from the post-pandemic period and quantified elasticities useful for poverty reduction policy simulation.